2007
DOI: 10.1002/ijc.23108
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette smoking and risk of borderline and invasive epithelial ovarian cancer

Abstract: Studies regarding the association between smoking and risk of epithelial ovarian cancer (EOC) are inconsistent. The purpose of this study was to examine the association between smoking and EOC, overall and according to invasiveness and histological subtype in a cohort of women with a high proportion of smokers at enrolment. We followed 103,081 women, aged 30-50 years in 1991/1992, from the Norwegian-Swedish Women's Lifestyle and Health cohort. The women completed a questionnaire on personal characteristics and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
27
1
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 27 publications
4
27
1
2
Order By: Relevance
“…Dagegen wirkt Rauchen bei BOT, nicht aber beim invasiven Ovarialkarzinom, bzw. nur bei den seltenen muzinösen Karzinomen als Risikofaktor [96,97]. Eine Zunahme des Rauchens bei Frauen in den 80er-Jahren könnte somit den Anstieg der relativen Häufigkeit der BOT mit erklären.…”
Section: Einleitung Epidemiologie Und Risikofaktorenunclassified
“…Dagegen wirkt Rauchen bei BOT, nicht aber beim invasiven Ovarialkarzinom, bzw. nur bei den seltenen muzinösen Karzinomen als Risikofaktor [96,97]. Eine Zunahme des Rauchens bei Frauen in den 80er-Jahren könnte somit den Anstieg der relativen Häufigkeit der BOT mit erklären.…”
Section: Einleitung Epidemiologie Und Risikofaktorenunclassified
“…These reports echo earlier studies that found current or recent smoking, along with a higher number of total pack-years of smoking, was associated with approximately a two-fold increase in risk of mucinous ovarian cancer compared to no or weak associations for non-mucinous ovarian cancers (811). In addition, studies examining the association between second-hand smoke exposure and risk of ovarian cancer are sparse, and reported a significant increased risk among never smokers for borderline tumors only (12), a significant decreased risk among never smokers (13) or no association of gestational or childhood environmental tobacco smoke exposure with the risk of invasive or borderline tumors among never smokers (14). …”
Section: Introductionmentioning
confidence: 99%
“…Whether the risk of other subtypes of ovarian cancer might also be influenced by cigarette smoking is less certain, as prior studies have not been uniform in their findings (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14).…”
mentioning
confidence: 99%